PREVALENCE AND PATTERN OF SELF MEDICATION TO PREVENT COVID-19 INFECTION: POPULATION-BASED SURVEY - GOHIL, TORAL; PATEL, ALPESH; PATEL, ZANKRUT; CHAUDHARY, VIPUL; PATEL, SUMIT (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objective: During COVID-19 pandemic, people have practiced one or more self-medication (SM) for prevention of the disease. This requires monitoring and evaluation to see the pattern of medicine used. Hence, in this study, we evaluated the prevalence and pattern of SM in various group of people. Methods: A cross-sectional study was conducted as an online survey on individuals who were in contact through mobile phone from October 2020 to March 2021. A pre-structured questionnaire-based Google form that contain questions related to SM practiced was prepared and circulated on social media application and email. Submitted forms were analyzed using Microsoft excel. Results: Out of 779 forms, 775 (99.4%) filled completely were considered in result. Majority (52%) of participants were in the age group of 20– 40 year. Six hundred and fifty-two (84%) participants had taken medication, out of which 40% were modern medicine users and rest 44% had used other than modern medicine. In modern medicine, Vitamin C was taken by 72% and in other group, lemon water was taken by 99% of participants. The prevalence of SM was highest among urban population (43%) with education up to postgraduation (53%). Health worker (57%) were highest among users. SM advice was received by doctors in 60% participants with belief of effectiveness against COVID-19 infection. Conclusion: SM was practiced by half of the participants that includes modern as well as other than modern medicine. It was mainly seen among people with higher education and who are associated with health-care system.